INVESTIGATING THE USE OF GAMFICATION IN READING COMPREHENSION - Septianto, Yoseph Dwi (Journal of English Teaching and Learning, 2025)
The lack of reading comprehension poses a significant challenge in developing countries such as Indonesia where the English Proficiency Index ranks the country at 79 which according to Education First is considered low. To address this issue the purpose of this study is to investigate the use of gamification in reading comprehension through a qualitative case study research design. This study involved the students of 3rd semester from one of the university in Banyuwangi, East Java with 38 total students. However, 24 students participated for open ended questionnaires and 7 students has consented and voluntarily become participants for one –on-one interview and focus group discussion. The data were analyzed quantitatively and qualitatively. The findings of this study revealed that gamification platform transform their classroom environment into more active and engaging affecting their reading comprehension by making them focus better and attentive towards the subject taught by the educator, key elements that strongly affected their reading comprehension is the competitive aspect particularly the leaderboard, challenges, and time limits. However due the time constraint contained within the gamification platform poses a challenge for deeper comprehension.